St. John’s Wort (Hypericum perforatum) Products – How Variable Is the Primary Material? - Scotti, Francesca; Löbel, Katja; Booker, Anthony; Heinrich, Michael (Frontiers in Plant Science, 2019)
Background: Saint John’s wort (Hypericum perforatum L., HP) is commonly registered in Europe under the THR scheme (Traditional Herbal Registration) or licensed as a medicine. Nonetheless unregulated medical products and food supplements are accessible through the internet which are often of poor quality. The species’ natural distribution stretches through large regions of Europe to China and four subspecies have been distinguished. When compared to the European Pharmacopoeia reference, the presence of additional compounds was linked to so-called Chinese HP. Aim: In order to obtain an integrated picture of the entire chemoprofile, the chemical composition of HP materia prima was studied using a combination of techniques well-established in the relevant industries. The impact of phytogeographic factors on the materia prima can shed light on whether the variability of the final products is strongly influenced by these factors of whether they relate to poor processing, adulteration, or other factors linked to the processing of the material. Methods: 86 Hypericum samples (77 H. perforatum) were collected from 14 countries. Most were authenticated and harvested in the wild; others came as roughly ground material from commercial cultivations, markets and pharmacies. The samples were analyzed using HPTLC and 1H-NMR-based PCA. Results and Discussion: Limited variability in the in chemical variability was found. Nonetheless, the typical fingerprint of Chinese HP was observed in each specimen from China. Additional compounds were also detected in some samples collected in Spain. Rutin is not necessarily present in the crude material. The variability previously found in the marketed products can be ascribed only partially to the geographical origin of harvested material, but mainly to the plant part harvested, closely related to harvesting techniques, processing and probably time of harvest. Conclusions: HP can be sourced in a consistent composition (and thus quality) from different geographical sources. However, chemical variability needs to be accounted for when evaluating what is considered authentic good material. Therefore, the processing and good practice are all stages of primary importance, calling for a better (self-)regulation and quality assurance along the value chain of an herbal medical product or botanical.